The Classical Neutrosophic Theory for Psychology and Education Measurement (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
The Paper aims to develop the concepts and assumptions of the classical theory of psychological and educational measurement in the light of Neutrosophic logic, and to lay the theoretical foundations for the theory of psychometric and educational Neutrosophic.